Fatores de risco, evolução clínica e tratamento das infecções em cirurgias ortopédicas com implantes - Inacio, Ricardo Cantarim [UNIFESP] (2019)
Introduction: surgical site infections have become a major worldwide problem and some reports from Brazilian hospitals show the third cause of infection related to health care (IRAS). With the increase in the number of orthopedic procedures with implants the surgical site infection in orthopedics has increased the morbidity of these patients, prolonging their hospitalizations and increasing hospital expenses. Finding measures that reduce the risk of infection in this population is of paramount importance to improve the quality of life of these patients, thus reducing their length of stay and the use of antimicrobials. Objectives: To evaluate the risk variables for the development of infection in orthopedic procedures with implants, the microorganisms that cause these infections, to compare more effective treatment measures and to evaluate the impact of reducing the epidemiological surveillance time in these infections. Patients and methods: A historical cohort study was carried out with the evaluation of all patients hospitalized at the General Hospital of Guarulhos from January 1st, 2016 to December 31th, 2016 and one year post-surgery follow-up for one year after surgery to assess whether infection developed. The patients were divided into exposed fractures, nonexposed fractures and arthroplasties. The groups were compared according to the infection diagnosis to evaluate preoperative, intraoperative and postoperative risk factors. A second part of the study compared patients who had infection within the group of exposed fractures and non-exposed fractures and assessed the clinical outcome after the proposed treatment: 1: conservative treatment: only with antimicrobial use; 2: surgical treatment: mechanical cleaning with maintenance of the synthesis material and with exchange or removal of the synthesis material. Infected microorganisms were evaluated in patients who developed acute infection (up to 30 days after osteosynthesis), subacute infection (30 to 90 days after osteosynthesis), and chronic infection (more than 90 days after osteosynthesis). Results: Exposed fracture had a higher infection rate than non-exposed fracture (16.56% and 6.55%, respectively, with p = 0.0002867 and a risk ratio of 2.52); antimicrobial use in the preoperative period of the first post-fracture bone stabilization was a protective factor (86.46% of the exposed fractures that infected received antimicrobial prophylaxis against 97.71% of exposed non-infected fractures, with p = 0.049), and use of gentamicin and clindamycin in patients with more severe exposed fractures classified as Gustillo & Anderson II and III were protective factors when compared to cefazolin use (p = 0.036). It was observed that patients with acute osteosynthesis infection had a higher risk of developing multiresistant gram-negative bacilli (81.71%), therefore, it was necessary to use broad-spectrum antimicrobials, which was not observed in patients with chronic infection, where most of the infectious agents identified were gram-positive and less resistant to antimicrobial agents (16.67% of multiresistant gram-negative bacteria, with p= 0.027). Conclusion: Performing adequate prophylaxis in the presence of exposed fracture in the emergency room, performing fracture stabilization and cleaning before eight hours after the exposed fracture should be extremely urgent measures to avoid infection. Patients with acute infection should have an antimicrobial coverage with a greater spectrum of empirical action until the result of the cultures because of the greater chance of these patients developing infection by multiresistant gram-negative bacteria, and also that there is a tendency to have more gram-negative bacteria causing infection of what was observed some years ago and which were described in the works.